Enzymatic Enrichment of Docosahexaenoic Acid (DHA) in Oil from EEL (Monopterus Albus) - Abdul Razak, Zainal Kifli (2003)
Docosahexaenoic acid, DHA is a polyunsaturated fatty acid that has shown some medical and health benefits At present, the most common sources of DHA are fish lipids The lipids of coldwater fishes are typically high in DHA and these lipids are widely used as food supplements However, for certain pharmaceutical and nutritional purposes, higher concentrations of DHA are required Thus, there is a need to enrich this fatty acid in those lipids which can be done by removal of other fatty acids Enzymatic method IS one of the popular methods for DHA enrichment of fish lipids in this research a local freshwater fish, the eel or Monopterus albus was analyzed for its lipid and fatty acid content The fatty acid content of the lipid was analyzed by gas chromatography after It was converted into methyl esters The lipid content of this fish was about 1% and this lipid contained about 6% of DHA.